Cerkiew prawosławna na Ukrainie i w Rosji po 2013 roku wobec wyzwań politycznych, konfliktu rosyjsko-ukraińskiego oraz pytań o granice suwerenności - Jędraszczyk, Katarzyna (My University, 2018)
The aim of the article is to analyse the place and importance of the Orthodox Church in the society and political culture of Ukraine after 2013. The new political realities following the “revolution of dignity”, the annexation of Crimea and the war in Donbas set new challenges for the Orthodox Church in Ukraine. Particularly important is the influence of the Russian Orthodox Church's authority over the Ukrainian Orthodox Church - Moscow Patriarchate. Artykuł stanowi analizę znaczenia i miejsca Kościoła prawosławnego w życiu społecznym i politycznym Ukrainy po 2013 r. Nowe realia polityczne po „rewolucji godności”, aneksji Krymu i wojnie w Donbasie postawiły przed Kościołem prawosławnym na Ukrainie nowe wyzwania. Szczególnie ważny okazuje się wpływ zwierzchnictwa Rosyjskiej Cerkwi Prawosławnej na podległą mu Ukraińską Cerkiew Prawosławną Patriarchatu Moskiewskiego.
Keywords: Ukrainian Orthodox Church-Moscow Patriarchate; Ukraińska Cerkiew Prawosławna Patriarchatu Moskiewskiego; Kyiv Patriarchate; political culture; Ukraine; church-state relations; national church; Ukraińska Cerkiew Prawosławna Patriarchatu Kijowskiego; kultura polityczna; Ukraina; polityka religijna; kościół narodowy